Review of the leafhopper genus Coloana Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) - Yang, Meixia; Cao, Yanghui; Zhang, Yalin (Zootaxa, 2014)
General characteristics of Coloana Dworakowska and a key to known species of the genus are provided. Six new species, Coloana accrescens, C. hainanensis, C. latiprocessa, C. orthoprocessa, C. recta and C. sinuata spp. nov. from China and Thailand are described and illustrated. C. cinerea Dworakowska is newly recorded from China.